CARBOPOL SEBAGAI GELLING AGENT YANG BAIK PADA FORMULASI SEDIAAN GEL FACIAL WASH EKSTRAK ETANOL DAUN KOPI ARABIKA (Coffea arabica L.) - Yahdian Rasyadi; Diza Sartika; Nadya Dini Fitri (Jurnal Insan Farmasi Indonesia, 2023)
Ethanol extract of arabica coffee leaves has various nutritious compounds such as flavonoids. With the existence of these beneficial compounds, extract can be developed into a facial wash gel so that it can be applied to facial skin care. In making facial wash gel, a gelling agent is required as a base to form a gel consistency. This study aims to determine the consistency of a good gel base in facial wash using the gelling agents Carbopol (F1 and F2), HPMC (F3 and F4) and Na CMC (F5 and F6). Results of the organoleptic test gel facial wash were blackish brown in color with a distinctive fragrance and semi-solid form on all formulation. The test results on the F1, F2, F3, F4, F5 and F6 obtained successive results of pH 4.68; 4.61; 4.76; 4.79; 4.67; and 4.67; viscosity 2468 cp; 3414 cp; 3420 cp; 3543 cp; 3379 cps and 3461 cps; foam stability 95.00%; 96.92%; 98.14%; 97.91%; 95.74% and 94.44%. Homogeneity and stability results show homogeneous and stable results in all formulas. Based on the research results, it can be concluded that all the formulas made meet the SNI requirements.